Simultaneous Determination of Caffeine and Chlorogenic Acids in Green Coffee by UV/Vis Spectroscopy - G. Navarra; M. Moschetti; V. Guarrasi; M. R. Mangione; V. Militello; M. Leone (Journal of Chemistry)
A simple method for the simultaneous determination of caffeine and chlorogenic acids content in green coffee was reported. The method was based on the use of UV/Vis absorption. It is relevant that the quantification of both caffeine and chlorogenic acids was performed without their preliminary chemical separation despite their spectral overlap in the range 250–350 nm. Green coffee was extracted with 70% ethanol aqueous solution; then the solution was analyzed by spectroscopy. Quantitative determination was obtained analytically through deconvolution of the absorption spectrum and by applying the Lambert-Beer law. The bands used for the deconvolution were the absorption bands of both caffeine and chlorogenic acids standards. The molar extinction coefficients for caffeine and chlorogenic acid in ethanol solution at 70% were calculated by using the chemical standards; the estimated values were ε(272 nm)=12159±97 M−1 cm−1 for caffeine and ε(330 nm)=27025±190 M−1 cm−1 for chlorogenic acids molecules, respectively. The estimate of concentration values was in agreement with the one obtained by High Performance Liquid Chromatography quantification. The method is fast and simple and allows us to realize routine controls during the coffee production. In addition, it could be applied on roasted coffee and espresso coffee.